Pengaruh Likuiditas, Leverage, Sales Growth, Dan Capital Intensity Terhadap Financial Distress: Peran Moderasi Profitabilitas Pada Perbankan Indonesia - Cyntara; Apriwandi Apriwandi (Owner : Riset dan Jurnal Akuntansi, 2025)
This study aims to analyze the effect of Liquidity, Leverage, Sales Growth, and Capital Intensity on Financial Distress, and to examine the moderating role of Profitability in banking sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2018–2023 period. The study uses a quantitative approach with a causal associative design. A total of 120 observations (20 companies × 6 years) were selected using purposive sampling, based on criteria of data completeness and consistency in financial reporting. The secondary data were obtained from company financial statements through documentation, and analyzed using the Moderated Regression Analysis (MRA) with SPSS. The findings show that Liquidity and Leverage significantly influence Financial Distress, while Sales Growth and Capital Intensity do not. Moreover, Profitability significantly moderates the relationship between Liquidity and Financial Distress, but not for the other variables. This study contributes to the predictive modeling of financial distress in the financial sector using financial ratios with a moderation approach, and emphasizes the importance of profitability management to prevent bankruptcy risk.